2022
DOI: 10.56353/aspiration.v1i2.13
|View full text |Cite
|
Sign up to set email alerts
|

The Journalists Has Built Self Meaning: Spreading Hate Speech in Presidential Election 2019 in Banten

Abstract: The current mass media industry is not the only sovereign of the source of informations. Based on technological advancements, social media exists as a blurring medium for space and time constraints in disseminating and exchanging information, but the minimal control mechanism causes content on social media is not only be positive, but also can be negative such as the spread of hate speech. Hate speech also enlivening journalist's Facebook accounts in Banten, especially during the 2019 Presidential Election cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Another discovery was that partners use alternative applications to chat and approach their prospective partners besides Instagram, especially experimenting to integrating stages (Putri, Andika, & Annisarizki, 2020). This study found that people in need of private space were more informal and social, like IMessage, WhatsApp, and LINE.…”
Section: Relationship Formationmentioning
confidence: 93%
“…Another discovery was that partners use alternative applications to chat and approach their prospective partners besides Instagram, especially experimenting to integrating stages (Putri, Andika, & Annisarizki, 2020). This study found that people in need of private space were more informal and social, like IMessage, WhatsApp, and LINE.…”
Section: Relationship Formationmentioning
confidence: 93%
“…Pendaftaran sekolah HN harus menempuh sebuah demografi dari siswa dimana mereka mengalami kesulitan untuk mengekspresikan identitas mereka sebagai etnis tertentu. Etnis yang berlawanan cenderung akan dikucilkan apabila mereka termasuk dalam etnis minoritas di dalam sebuah kelompok (Putri et al, 2020).…”
Section: Kesadaran Magis Pada Proses Rekonsiliasi Konflikunclassified
“…This letter covers all actions that fall under the category of hate speech according to the Criminal Code (KUHP) and all actions that fall under other non-criminal provisions. These actions include discrimination, defamation, insults, discomfort, provocation, incitement, and spreading fake news (Putri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%